2019
DOI: 10.1016/j.addbeh.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and gender minority young adults' smoking characteristics: Assessing differences by sexual orientation and gender identity

Abstract: Smoking characteristics were mostly similar across sexual and gender identities. • Transgender individuals smoked more cigarettes per day than cisgender or nonbinary. • Nonbinary participants smoked less than transgender or cisgender participants. • Lesbians initiated regular smoking later than "other" sexual identity individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Previous studies on cigarette/e-cigarette use among transgender populations have not examined this subgroup. [10][11][12][13][14]16,17,25 There is lack of consensus about the inclusion of crossdressers under the transgender umbrella, as these individuals may not experience gender dissonance and cross dressing is regarded as a form of gender expression rather than indicative of gender identity. 44,45 They were included in this study to acknowledge the diverse identities within the gender spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on cigarette/e-cigarette use among transgender populations have not examined this subgroup. [10][11][12][13][14]16,17,25 There is lack of consensus about the inclusion of crossdressers under the transgender umbrella, as these individuals may not experience gender dissonance and cross dressing is regarded as a form of gender expression rather than indicative of gender identity. 44,45 They were included in this study to acknowledge the diverse identities within the gender spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies using national probability samples have found that gender minority status was not associated with increased likelihood of current smoking or e-cigarette use. [10][11][12] However, other studies also suggest that transgender individuals were more likely to be current smokers than cisgender people [13][14][15] and that transgender men and boys had increased odds of current smoking compared with cisgender men and boys. 16,17 Studies of sexual and gender minorities have also documented the elevated rates of cigarette smoking among transgender people compared to their cisgender counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement and coding details were reported previously. 32 In the TSP trial, from which the historical control groups were drawn, response options for sexual identity were, "straight (heterosexual)," "lesbian/gay (homosexual)," "bisexual," or "not listed (please specify)." Response options for gender identity were "male," "female," or "transgender."…”
Section: Baseline Measuresmentioning
confidence: 99%
“…Cross-tabulations of sexual and gender identity in the present trial were reported previously. 32 In the historical control conditions, participants were 0.7% straight (n = 1), 27.4% lesbian/gay (n = 37), 63% bisexual (n = 85), and 8.9% other sexual identity (n = 12). Gender identity of the historical control group sample was 65.9% (n = 89) female, 31.9% (n = 43) male, and 2.2% (n = 3) transgender.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…The development of sexual identity is a di cult, complex, multidimensional process [37]. As an important factor of MSMs' mental health, among different types of sexual minority, the effect of sexual minority identity on risky behavior is different and enhances the rise [38][39][40]. While "coming out" is typically stressful for YMSMs, it is also associated with positive mental health and identity outcomes, especially in the long run [41].…”
Section: Introductionmentioning
confidence: 99%